Edutainment sebagai Strategi Komunikasi Pembangunan dalam Media Digital: Analisis Teori Sabido pada Konten YouTube Watchdoc Documentary “Tanah Moyangku” - Nina Kusumawati (Journal of Innovative and Creativity, 2025)
Digital media is currently a primary means of development communication. Edutainment, a combination of education and entertainment, is an effective strategy for conveying social messages in an engaging manner. This study analyzes the content of the YouTube Watchdoc documentary "Land of My Ancestors" through the Sabido theory framework, which emphasizes the influence of dramatic media on changing audience attitudes and behavior. The results show that the use of dramatic narratives, representative characters, and emotional storylines can raise public awareness of agrarian conflict issues and encourage social participation.